Anxiety among Patients undergoing Hemodialysis attending at Hemodialysis Unit of Birat Medical College Teaching Hospital - Karki, Rina; Sah, Dilip Kumar; Kunwor, Sharada; Bhattarai, Amrita; Raut, Anisha; Bhattarai, Smita (Birat Journal of Health Sciences, 2025)
Introduction: Anxiety is a common problem experienced by patients with chronic kidney failure undergoing hemodialysis therapy. Hemodialysis can be a challenging experience for patients, often leading to psychological distress, including anxiety which may vary from mild, moderate, severe to panic. Objectives: To find out the prevalence of anxiety among hemodialysis patient and its association with selected socio-demographic and clinical variables. Methodology: The study used a descriptive cross-sectional research design. A total, 108 hemodialysis patients were chosen using a non-probability purposive sampling method. Anxiety symptoms were assessed using Hamilton Anxiety Rating Scale. Data was collected using face-to-face interview method. SPSS version 20 was used for data analysis. Results: The mean age of the participants was 48.44 years ranging from 20 to 81 years. More than one-third (38.9%) of the participants belonged to the age group 45-59 years. More than half (54.6%) were females. About one-third had mild anxiety symptoms. Hemodialysis duration showed significant (p<0.05) association with anxiety. Conclusion: The study concluded that nearly one fourth of the respondents had no anxiety symptoms whereas about one-third had mild anxiety symptoms. Likewise, one-fourth of the respondents had severe anxiety symptoms. Hence, psychosocial counselling and collaborative treatment approach is needed to reduce the anxiety symptoms among the hemodialysis patient.